The Study Collection of Figurative Terracottas in the Metropolitan Museum of Art: A Critical Review - Jaimee Uhlenbrock (Les Carnets de l’ACoSt)
The Study Collection at the Metropolitan Museum of Art includes over Greek 200 figurative terracottas. Committed to the accessibility of its collections to a wider audience, The Metropolitan Museum of Art has nearly emptied its storerooms of portable antiquities and set these objects on public display in a dedicated gallery. Although little information on these terracottas, vases, minor sculptures, and coins is provided in this gallery, the lack of this information does not particularly hinder the ability to engage with these objects for study purposes that then can provide the foundation for further research.